Two new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) in China - Di, Juan-Xia; Han, Li; Mao, Shao-Li; Shi, Fu-Ming (Zootaxa, 2015)
Two new species of the genus Xizicus are described, namely Xizicus (Eoxizicus) uncicercus Mao & Shi sp. nov. and Xizicus (Eoxizicus) dischidus Di, Han & Shi sp. nov. from China, in addition, photographs of morphological structure of the species are provided. All type specimens are deposited in the Museum of Hebei University, Baoding, P. R. China.